Efficient wideband gain modeling for interferometric imaging arrays in radio astronomy - Young, A.; Davidson, David; Wijnholds, S.; Carozzi, T.; Maaskant, R.; Ivashina, M. (2015)
© 2015 IEEE. Current and future interferometric imaging arrays in radio astronomy may be limited by the accuracy with which various direction-dependent effects, such as the antenna gain patterns, can be corrected. Doing this in an efficient manner during the calibration and imaging process is especially difficult due to these effects often being also baseline-dependent. A newly proposed method, called A-stacking, offers a solution through the use of a parametrized model in which basis functions account for the direction-dependence and the expansion coefficients account for the baseline-dependence. This approach provides a simple trade-off between computational complexity and calculation accuracy. Herein the use of the A-stacking method to model direction-dependent effects over a very wide frequency band is investigated.